Penerapan Video Pembelajaran Berbasis Animasi 2D Dasar Desain Grafis Menggunakan Aplikasi Corel Draw Untuk Meningkatkan Kemampuan Kognitif Siswa: Application Of Basic 2D Animation-Based Learning Video For Graphic Design Using Corel Draw Application To Improve Student’s Cognitive Abilities - Veronica Kristiani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Education is a place to change attitudes or a place to hone abilities from the teraching and training received, but it cannot be denied that students’ cognititve abiities are still lacking. The aim of this research is to determine the result of implementing basic 2D animation-basic learning videos for graphi desing using the Corel Draw application to improve students’ cognitive abilities. Data is collected through the systematic literature review (SLR) method by identifying, evaluating and interpenting all research that is relevant to the problem formulation or topic area being researched. From the result obtained, it can be concluded that students’ cognitive abilities can incrase by using Corel Draw.